Shielding of Photosynthetic Apparatus by Consortia of Bacterial Endophytes in Tomato Plants Suffering From Fusarium Wilt - Chaturvedi, Himani; Singh, Bhupendra; Jajoo, Anjana; Prakash, Anil (Frontiers in Agronomy, 2022)
Fusarium oxysporum is one of the most damaging plant pathogens causing Fusarium wilt in many plants leading to serious economic loses. The fungus colonizes xylem which leads to resistance in water flow in the plant thereby affecting the rate of photosynthesis. Present study focuses on selection of bacterial endophytes isolated from tomato plants and evaluating their potential to antagonize Fusarium oxysporum in tomato in-vivo. The results in the study indicated that two endophytic isolates identified as Pseudomonas fluorescens BUMD5 and Bacillus velezensis BUMD9 could act as efficient biocontrol agents (BCAs). Both the isolates were found to produce hydrolytic enzymes chitinase and protease. They were also demonstrated to be positive for siderophore and hydrogen cyanide (HCN) production. It was observed during the study that the consortia of both the isolates significantly reduced the infection percentage and disease severity. The plants treated with the isolates were exhibited better plant growth overall despite being infected by the pathogen. Furthermore, the treatment of infected plants with these potent isolates was also beneficial in improving the overall photosynthetic performance index (PI).